POST-FLOOD ASSESSMENT OF THE PHYSICO-CHEMICAL PARAMETERS OF TROPICAL MAN-MADE LAKE IN NORTHEASTERN NIGERIA - Umar, Abubakar; Garba, A. I.; Shehu, A.; Nasir, A.; Musa, A. Y; Yusufu, I. I.; Gadaka, Y. M.; Abdulazeez, K. A. (FUDMA Journal of Sciences, 2025)
This study evaluated key physico-chemical parameters of Lake Alau, Borno State, Nigeria, to assess its suitability for fisheries and domestic uses. Were collected fortnightly from May to June 2025 between 7:00 and 9:00 am at three fixed stations using one-liter PVC bottles. In-situ measurements of temperature and pH were taken with a Hanna HI98129 Portable Multi‑Parameter Meter, while other parameters were analyzed at FCFFT Baga using standard AOAC, APHA, and WHO methods. Parameters analyzed monthly included dissolved oxygen, carbon dioxide, biological oxygen demand, alkalinity, nitrate, phosphate, turbidity, total dissolved solids, and conductivity. Data were statistically analyzed using ANOVA and Duncan’s Multiple Range Test (DMRT) at p < 0.05 via Statistix 10.0. Results (mean ± SE, range) indicated: temperature (26.1 ± 0.4 °C, 25.5–26.7 °C), depth (3.4 ± 0.2 m, 3.1–3.6 m), pH (7.4 ± 0.1, 7.2–7.6), dissolved oxygen (6.2 ± 0.3 mg/L, 5.8–6.6 mg/L), BOD (3.1 ± 0.2 mg/L, 2.7–3.4 mg/L), nitrate (1.8 ± 0.2 mg/L, 1.5–2.1 mg/L), phosphate (0.35 ± 0.05 mg/L, 0.30–0.40 mg/L), turbidity (12.4 ± 1.2 NTU, 11.0–13.8 NTU), TDS (225 ± 15 mg/L, 210–240 mg/L), and conductivity (390 ± 25 µS/cm, 360–420 µS/cm). All values fell within permissible limits set by FAO, SON, and WHO, except phosphate, which marginally exceeded WHO’s recommended <0.3 mg/L. Temperature correlated positively with most parameters (r = 0.52–0.78, p < 0.05). This baseline indicates Lake Alau’s continued suitability for fisheries and domestic use while highlighting minor nutrient enrichment that warrants regular monitoring and community-based pollution management